1996
DOI: 10.1002/chin.199609238
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Efficient kg‐Scale Synthesis of Thrombin Inhibitor CRC 220.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 100 leading journals. To access a ChemInform Abstract of an article which was published elsewhere, please select a “Full Text” option. The original article is trackable via the “References” option.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 1 publication
0
11
0
Order By: Relevance
“…Careful thought had to be given to the sequence and how high ee could be attained due to the relatively hydrolytically labile nitrile group, which is subsequently converted to the amidine moiety of 152. 201 In another example Rh-(S,S)-EtDuPhos (Rh-13b) gave high enantioselectivity (>98%) with the fluorosubstituted amino esters 154a-c even though the substrates were E/Z-mixtures. 202 With an additional b-substituent, b-trifluoromethyl a-amino acids can be prepared by an asymmetric reduction in the presence of Rh-TCFP (Rh-124).…”
Section: Substrate Screeningmentioning
confidence: 99%
“…Careful thought had to be given to the sequence and how high ee could be attained due to the relatively hydrolytically labile nitrile group, which is subsequently converted to the amidine moiety of 152. 201 In another example Rh-(S,S)-EtDuPhos (Rh-13b) gave high enantioselectivity (>98%) with the fluorosubstituted amino esters 154a-c even though the substrates were E/Z-mixtures. 202 With an additional b-substituent, b-trifluoromethyl a-amino acids can be prepared by an asymmetric reduction in the presence of Rh-TCFP (Rh-124).…”
Section: Substrate Screeningmentioning
confidence: 99%
“…Precipitation from the reaction mixture increased the selectivity to > 99.8% ee; this process has been scaled up to 10 kg (Scheme 1.16 ) [120] .…”
Section: Synthesis Of Pharmaceutical Intermediatesmentioning
confidence: 99%
“…Reaction of 6 with hydroxylamine in ethanol at low temperature furnished the desired amidoxime 7 in excellent yield. The nitrile to amidoxime transformation is routinely performed at reflux 22 , however, we found that reaction of 6 with hydroxylamine at temperatures above 0°C resulted in benzyl ester cleavage.…”
mentioning
confidence: 90%